An Investigation on Students’ Ability Through Images (Pictures) in Writing Spoof Text: A Case on Teaching Strategy - Sinaga, Yanti Kristina; Herman, Herman; Simajuntak, Naomi (Journal of English Language and Education, 2025)
This study investigates the effectiveness of using images (pictures) as a teaching strategy to enhance students’ ability in writing spoof texts. The research was conducted at SMA Swasta Kampus Nommensen Pematang Siantar during the 2024/2025 academic year, involving two classes of eleventh-grade students. A quasi-experimental design was employed, with one class assigned as the experimental group and the other as the control group. The experimental group received image-based instruction, while the control group was taught using traditional methods. Data were collected through pre-tests and post-tests to measure students’ writing abilities before and after the intervention. The results revealed a significant improvement in the experimental group’s performance. Their average score increased from 52.61 (pre-test) to 84.19 (post-test), whereas the control group’s average rose modestly from 51.77 to 66.54. The statistical analysis using a t-test yielded a value of 6.06, exceeding the critical value of 2.00 at a 0.05 significance level, indicating a meaningful difference between the two groups. These findings suggest that visual aids can effectively support students in understanding and composing spoof texts by stimulating creativity, aiding in idea development, and improving structural coherence. The study concludes that integrating images into writing instruction significantly enhances students' writing performance and recommends this approach for teaching narrative genres that require imagination and structure.